Malaria Vaccines and Global Equity: A Scoping Review of Current Progress and Future Directions - Rajesh Perumbilavil Kaithamanakallam; Tirath Patel; Bharati Balachandran; Neville Fernandez; Joseph Jillwin; Dharambir Kashyap; Aparna Shivaprasad; Uttam Udayan; Pragnesh Kalyandrug; Aakanksha Aakanksha; Prasanna Honnavar (Biomedicines)
The journey toward a viable malaria vaccine, initiated in 1965, reached a major milestone in 2021 with the WHO’s endorsement of RTS,S/AS01, a recombinant protein-based malaria vaccine. This progress continued with the 2023 approval of the R21/Matrix-M vaccine, which is more cost-effective, more potent due it is higher protein content, and easier to manufacture. Though these achievements signal hope, malaria’s intricate life cycle and its prevalence in underprivileged regions make vaccine development and equitable distribution challenging. This review explains the lifecycle of malaria and explores the evolution of various treatment strategies aimed at reducing malaria-related mortality. This scoping review aims to provide a comprehensive overview of malaria vaccines, examining their development, efficacy, safety, and implementation challenges. Using a structured literature search across PubMed, Web of Science, and Scopus, we identified key themes related to malaria vaccines trials, policy implications, and future research needs. Peer-reviewed publications on PubMed, Scopus, and Web of Science from 1970 to 2024 were searched without any limitations. Search and Boolean search terms were modified to include terms like “malaria vaccines”, “malaria vaccination”, “malaria immunisation”, “malaria immunisation AND malaria-endemic countries”, “malaria endemic low-income countries AND malaria control”, “malaria public health control”, “malaria chemoprophylaxis AND early diagnosis of malaria”, “screening for malaria”, and “laboratory diagnosis of malaria in endemic countries” in order to find pertinent studies. Preliminary insights suggest that although vaccines are crucial, comprehensive strategies involving health education, hygiene, and timely medical intervention remain essential to malaria control.